Syariah Card Perspektif Al-Makasid Syariah - Ulul Azmi Mustofa (ITB AAS INDONESIA Surakarta, 2015)
Islamic Banking in this era is booming. Also its product, such as product Syariah Card (Islamic Credit Card). This paper examines a system and concept Syariah Card with al-Maqhasid Syariah Perspective. We found a Syariah card concept is acceptable with Fiqh concept, but there are many qualifyings. One of The qualifying is must consumer priority, meaning is consumer not be improvident.Key Word : Syariah Card, al-Maqhasid Syariah